Preparation of a gel ball-loaded sulfur cluster multi-level porous MOFs composite material and its application in removing Hg(II) from water
By modifying sulfur-containing functional groups on the MOFs material and building a multi-stage pore structure, and using guar gum to form a gel ball structure, the problem of poor mass transfer efficiency and structural stability of MOFs-based adsorption materials in complex water environments is solved, and efficient cyclic adsorption of Hg(II) and good recycling of materials are achieved.
Patent Information
- Application Number
- CN202411357196.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-09-27
AI Technical Summary
The existing MOFs-based adsorbent materials have poor mass transfer efficiency and structural stability in complex water environments, making it difficult to achieve recycling.
By modifying the sulfur-containing functional groups and building a multi-stage pore structure, a gel ball-loaded sulfur cluster multi-stage pore MOFs composite was prepared, and a guar gum mixing strategy was used to form a gel ball structure to stabilize the loading material, and solve the problem of easy loss of powder materials.
It realizes efficient cyclic adsorption of Hg(II) in complex water environments, maintains the mass transfer efficiency and structural stability of the material, improves the adsorption capacity and adsorption rate, and has good recycling capabilities.
Smart Images

Figure CN118988266B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of mercury removal in water bodies, and in particular to the preparation of a gel ball-loaded sulfur cluster multi-level porous MOFs composite material and its application in removing Hg(II) from water. Background Art
[0002] Heavy metal pollution in the aquatic environment is an important part of water pollution. Mercury is one of the only two heavy metals (the other is arsenic) that can complete the earth's biochemical cycle and is easily enriched in the human body. Mercury mainly exists in the form of inorganic Hg(II) in water bodies. Currently, commonly used removal technologies include coagulation and precipitation, ion exchange, bioremediation, membrane separation, adsorption, etc. Among them, the adsorption method is widely used for the adsorption and removal of Hg(II) due to its simple operation, low cost, and high removal efficiency.
[0003] At present, researchers are trying to use metal-organic frameworks (MOFs) as carriers to modify specific sulfur-containing functional groups for Hg(II) adsorption and removal. Although this method solves the problems of material adsorption selectivity and adsorption efficiency, since the thiol functional group is an organic molecule, it often occupies the internal space of the material pores after modification in the internal pores of the material, thereby affecting the mass transfer efficiency inside the material. In actual water environments, coexisting anions and cations, dissolved organic matter, etc. will also enter the internal pores of the material during the adsorption process, thereby affecting the adsorption performance of the material. In addition, water environmental factors such as pH will also affect the activity of the thiol functional group, thereby affecting the Hg(II) removal efficiency of the material. In actual applications, a single MOFs powder material will gradually be lost under the action of water flow as it is used, which is not conducive to recycling.
[0004] Based on the above problems, the existing MOFs-based adsorption materials have poor mass transfer efficiency and structural stability, and cannot be applied to recycling in various harsh environments such as natural water bodies. Summary of the invention
[0005] The present invention provides a preparation method of a gel ball-loaded sulfur cluster multi-level porous MOFs composite material and its application in removing Hg(II) from water. The gel ball-loaded sulfur cluster multi-level porous MOFs composite material has high mass transfer efficiency and rich sulfur active sites by modifying sulfur-containing functional groups and constructing a multi-level porous structure. The gel ball structure formed by the guar gum mixing strategy can effectively stabilize the internal sulfur cluster multi-level porous MOFs; at the same time, the material after gel stabilization loading effectively solves the problems of easy loss and difficult recovery of powder materials. The finally obtained gel ball-loaded sulfur cluster multi-level porous MOFs composite material can realize cyclic, rapid and large-scale adsorption of Hg(II).
[0006] In order to achieve the above object, the present invention provides the following technical solutions:
[0007] The present invention provides a gel ball loaded sulfur cluster multi-level porous MOFs composite material, comprising a skeleton and a guar gum gel layer wrapped on the skeleton, wherein the mass ratio between the skeleton and the guar gum gel layer is (0.5-1.5):(2.15-16.35); the skeleton is composed of a multi-level porous UiO-66 material modified with sulfur clusters, and the multi-level porous UiO-66 material has micropores and mesopores.
[0008] The MOFs composite material obtained by modifying sulfur-containing functional groups and constructing a multi-level pore structure has a richer pore structure. When facing a complex water environment (such as coexisting anions and cations, dissolved organic matter, strong acid and strong base environment, etc.), it can effectively avoid the pores from being occupied, ensuring the mass transfer efficiency of the MOFs composite material and the accessibility of sulfur active sites. Furthermore, the use of gel balls to stably load the material effectively solves the problems of easy loss of powder materials and difficulty in recycling and reuse, and improves the Hg (II) adsorption capacity and adsorption rate of the material.
[0009] The amount of the guar gum gel layer used is not the same as the amount of the guar gum gel layer actually synthesized, and part of the guar gum gel cannot adhere to the surface of the skeleton to form a guar gum gel layer.
[0010] Preferably, the modification amount of the sulfur clusters is 4-5%wt, the pore diameter of the mesopores is 2.5-4.5 nm, and the number ratio of the micropores to the mesopores is (1.8-2.2):1.
[0011] The present invention also provides a method for preparing a gel ball-loaded sulfur cluster multi-level porous MOFs composite material, comprising:
[0012] S1. Adding UiO-66 with mixed ligands to ammonium tetrathiomolybdate solution, mixing evenly, reacting, freeze-drying, and calcining to obtain sulfur cluster-modified hierarchical porous UiO-66;
[0013] S2. The mixed solution obtained by mixing the sulfur cluster modified hierarchical porous UiO-66 obtained in S1 with the guar gum solution is dropped into a sodium tetraborate solution to obtain a gel ball material. After washing and collection, the gel ball loaded sulfur cluster hierarchical porous MOFs composite material is obtained by freeze-drying.
[0014] The present invention removes part of the ligands in UiO-66 with mixed ligands during the calcination stage, thereby constructing a mesoporous structure of about 4 nm while retaining the microporous structure of UiO-66; and 2-During the calcination stage, it is transformed into more stable molybdenum polysulfide clusters, which effectively anchors the sulfur active sites in the material and ensures the stability of sulfur cluster-modified hierarchical porous UiO-66.
[0015] On this basis, the powdered sulfur cluster-modified hierarchical UiO-66 was loaded into guar gum gel balls by utilizing the uniform encapsulation effect of the gel, so that the powder material is not easily lost during the adsorption process, ensuring the recyclability of the adsorbent. The guar gum loading process uses the drop ball method, without the need to introduce additional cross-linking agents, and guar gum has good hydrophilicity and will not be overly tightly aggregated, thereby improving the adsorption capacity and adsorption rate of the obtained gel ball-loaded sulfur cluster hierarchical MOFs composite material.
[0016] Preferably, in S1, the preparation method of UiO-66 with mixed ligands comprises: dissolving a zirconium source, a stable ligand, and an unstable ligand in an organic solvent, adding an acetic acid aqueous solution, mixing, and then performing a hydrothermal reaction.
[0017] More preferably, the molar ratio of the zirconium source, the stable ligand and the unstable ligand is 10:(3-7):(3-7).
[0018] Further preferably, the molar ratio of the zirconium source, the stable ligand and the unstable ligand is 10:7:3.
[0019] More preferably, the stabilizing ligand is terephthalic acid, and the unstable ligand is 2-aminoterephthalic acid.
[0020] More preferably, the zirconium source is a zirconium salt.
[0021] More preferably, the zirconium salt is zirconium chloride.
[0022] More preferably, the organic solvent is N,N-dimethylformamide.
[0023] More preferably, the hydrothermal reaction conditions are 110-130° C. for 24-36 hours.
[0024] Further preferably, the hydrothermal reaction condition is 120° C. for 24 h.
[0025] Further preferably, the acetic acid aqueous solution is prepared by mixing acetic acid and deionized water in a volume ratio of (2.5-3):0.02.
[0026] Preferably, in S1, the reaction conditions are 70-100° C. for 24-48 h; and the calcination conditions are 340-400° C. for 2-4 h.
[0027] Preferably, in S2, the dry weight ratio of sulfur cluster modified hierarchical porous UiO-66, guar gum and sodium tetraborate is (0.5-1.5): (0.15-0.35): (2-16).
[0028] Further preferably, in S2, the dry weight mass ratio of sulfur cluster modified hierarchical porous UiO-66, guar gum and sodium tetraborate is (0.5-1.5):0.15:(2-7).
[0029] Further preferably, in S2, the dry weight ratio of sulfur cluster modified hierarchical porous UiO-66, guar gum and sodium tetraborate is (0.5-1.5):0.15:(4-6).
[0030] Further preferably, in S2, the dry weight ratio of sulfur cluster modified multi-level porous UiO-66, guar gum and sodium tetraborate is 1:0.15:(4-6).
[0031] Further preferably, in S2, the dry weight ratio of sulfur cluster modified hierarchical porous UiO-66, guar gum and sodium tetraborate is 1:0.15:4.
[0032] The present invention also provides the use of the gel ball-loaded sulfur cluster multi-level porous MOFs composite material or the gel ball-loaded sulfur cluster multi-level porous MOFs composite material prepared by the above preparation method in removing Hg(II) from mercury-contaminated water.
[0033] Preferably, the mercury-contaminated water is a natural water body containing mercury; the temperature of the natural water body containing mercury is 15-35° C., the pH is 1-12, and it contains a variety of anions, a variety of cations, and a variety of organic matter.
[0034] The present application simulates natural water bodies in the laboratory, specifically, by adding multiple anions, multiple cations, multiple organic matter and controlling the pH in the deionized water sample containing mercury to simulate the natural water environment. The results show that: under the interference of other coexisting anions, cations and organic matter, or under extreme pH values, the material obtained in the present application can still maintain a stable adsorption removal efficiency.
[0035] Further preferably, the anion comprises HCO3 - ,PO4 3- , SO4 2- and Cl - .
[0036] Further preferably, the cation includes Na + , K + , Ca 2+ ,Mg 2+ , Cu 2+ , Cd 2+, Zn 2+ , Ni 2+ and Pb 2+ .
[0037] Further preferably, the organic matter includes humic acid and fulvic acid.
[0038] Preferably, the mercury-contaminated water is industrial wastewater containing mercury; the pH of the industrial wastewater is 0.68-1.6.
[0039] The present application was tested using actual industrial wastewater, and it was found that the material obtained in the present application also performed excellently in treating actual industrial wastewater.
[0040] Preferably, the gel ball-loaded sulfur cluster multi-level porous MOFs composite material can cyclically adsorb and remove mercury-contaminated water.
[0041] The removal rate of mercury-contaminated water with 10 ppm Hg(II) reached 90% after 5 cycles, and remained above 80% after 10 cycles, proving that the gel ball-loaded sulfur cluster multi-level porous MOFs composite material provided in the present application has the ability of cyclic adsorption.
[0042] Therefore, the present invention has the following beneficial effects:
[0043] (1) The gel ball-loaded sulfur cluster multi-level porous MOFs composite material provided by the present invention has high mass transfer efficiency and high structural stability, and can achieve efficient cyclic adsorption of Hg(II) in complex water environments.
[0044] (2) The present invention utilizes the difference in stability between terephthalic acid and 2-aminoterephthalic acid, removes the unstable 2-aminoterephthalic acid structure under high-temperature calcination to obtain multi-level porous UiO-66, and utilizes the multi-level porous structure of multi-level porous UiO-66 to solve the interference of dissolved organic matter and coexisting anions and cations in complex water environments, thereby ensuring the mass transfer efficiency of the gel ball-loaded sulfur cluster multi-level porous MOFs composite material.
[0045] (3) The present invention uses high temperature calcination to simultaneously convert unstable MoS4 into a porous UiO-66. 2- It is transformed into more stable molybdenum polysulfide clusters, thereby effectively anchoring the sulfur active sites in the material and ensuring the stability of the active sites in the sulfur cluster-modified hierarchical porous UiO-66.
[0046] (4) The present invention uses guar gum as the gel raw material, and no additional cross-linking agent needs to be introduced during the preparation process. Guar gum has good hydrophilicity and will not undergo excessively tight polymerization, thereby improving the adsorption capacity and adsorption rate of the obtained gel ball-loaded sulfur cluster multi-level porous MOFs composite material. BRIEF DESCRIPTION OF THE DRAWINGS
[0047] Figure 1 The BET graphs of the sulfur cluster multi-level porous MOFs composite material obtained in Example 1 before and after calcination, wherein a is a BET curve graph and b is a pore size distribution graph;
[0048] Figure 2 The actual pictures of the materials obtained with different dosages of guar gum and sodium tetraborate;
[0049] Figure 3 It is a bar graph of the deep removal efficiency and adsorption capacity of the materials obtained under different guar gum and sodium tetraborate dosages, and the abscissa is the sodium tetraborate dosage;
[0050] Figure 4 The actual pictures of the materials obtained with different dosages of sodium tetraborate and different MOF materials;
[0051] Figure 5 It is a bar graph of the deep removal efficiency and adsorption capacity of the materials obtained under different dosages of sodium tetraborate and different MOF materials, and the horizontal axis is the dosage of sodium tetraborate;
[0052] Figure 6 The SEM images and physical images of the materials obtained at different MOF material dosages, wherein a, b, and c are respectively the SEM images and physical images of Example 32 at different magnifications, d, e, and f are respectively the SEM images and physical images of Example 33 at different magnifications, and g, h, and i are respectively the SEM images and physical images of Example 34 at different magnifications;
[0053] Figure 7 The BET diagrams of the materials obtained at different MOF material dosages, where a is the BET curve diagram and b is the pore size distribution diagram;
[0054] Figure 8 It is the adsorption thermodynamic diagram of the materials obtained at different MOF material dosages;
[0055] Fig. 9 This is the adsorption thermodynamic diagram of sodium alginate gel ball material under different MOF material dosages;
[0056] Fig.10 This is the adsorption kinetics diagram of sodium alginate gel sphere and guar gum gel sphere;
[0057] Fig.11 The XRD diagram of the material obtained in Example 1 before and after adsorption;
[0058] Fig.12 This is a diagram of the adsorption of the material obtained in Example 1 under the influence of different temperatures;
[0059] Fig.13 This is a diagram of the adsorption of the material obtained in Example 1 under the influence of different pH values;
[0060] Fig.14 This is a diagram showing the adsorption of the material obtained in Example 1 under the influence of coexisting cations;
[0061] Fig.15 This is the adsorption selection diagram of the material obtained in Example 1 for different cations;
[0062] Fig.16 The adsorption of the material obtained in Example 1 under the influence of coexisting anions, where a is HCO3 - , b is PO4 3- ,c is SO4 2- , d is Cl - ;
[0063] Fig.17 This is a diagram of the adsorption of the material obtained in Example 1 under the influence of organic matter, where a is humic acid and b is fulvic acid;
[0064] Fig.18 This is a diagram showing the adsorption of industrial wastewater by the material obtained in Example 1;
[0065] Fig.19 This is a diagram of the cyclic adsorption performance of the material obtained in Example 1. DETAILED DESCRIPTION
[0066] The present invention is further described below in conjunction with specific embodiments. Those of ordinary skill in the art will be able to implement the present invention based on these descriptions. In addition, the embodiments of the present invention involved in the following description are generally only embodiments of a part of the present invention, rather than all embodiments. Therefore, based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work should fall within the scope of protection of the present invention.
[0067] [Example]
[0068] Example 1
[0069] S1. Preparation of UiO-66 with mixed ligands: At room temperature, 0.2331 g (1 mmol) of zirconium chloride was fully dissolved in 10 mL of N, N-dimethylformamide to obtain a zirconium chloride solution, and 0.1163 g (0.7 mmol) of terephthalic acid and 0.0544 g (0.3 mmol) of 2-aminoterephthalic acid were fully dissolved in 10 mL of N, N-dimethylformamide to obtain a mixed ligand solution. The mixed ligand solution was added to the zirconium chloride solution, and then 2.86 mL (50 mmol) of acetic acid and 20 μL of deionized water were added thereto to obtain a precursor solution. After ultrasound, the precursor solution was transferred to a hydrothermal reactor and placed in a 120°C oven for reaction for 24 hours. The product obtained after the reaction was centrifuged and washed twice in N, N-dimethylformamide, methanol, and deionized water, respectively, and then placed in a freeze dryer for freeze drying for 24 hours to obtain a UiO-66 material with mixed ligands.
[0070] S2. Preparation of sulfur cluster modified hierarchical pore UiO-66: 40 mg of ammonium tetrathiomolybdate was dissolved in 20 mL of deionized water, and 100 mg of UiO-66 material with mixed ligands obtained in S1 was added thereto. After ultrasonic oscillation, magnetic stirring was performed at room temperature to obtain a mixed solution, and then the mixed solution was transferred to an 80°C oven for reaction for 24 hours. The obtained product was ultrasonically washed 3 times with deionized water, then placed in a freeze dryer for 24 hours, and then subjected to high temperature treatment at 350°C for 2 hours to obtain sulfur cluster modified hierarchical pore UiO-66, recorded as HP-UiO-66-MoS4.
[0071] S3, preparation of gel ball loaded sulfur cluster multi-level porous MOFs composite material: take 150mg guar gum and dissolve it in 20mL water, then add 1g HP-UiO-66-MoS4 material obtained by S2, and stir magnetically to obtain a mixed solution. Take 4g sodium tetraborate and dissolve it in 400mL water, and stir magnetically slowly at room temperature. Use a syringe to absorb the mixed solution containing HP-UiO-66-MoS4, and slowly add it dropwise to the prepared sodium tetraborate solution to obtain brown gel balls. After the obtained gel balls are stirred and washed twice with pure water, they are placed in a freeze dryer and freeze-dried for 48h to obtain a gel ball loaded sulfur cluster multi-level porous MOFs composite material, wherein the sulfur cluster modification amount is 4.48%wt, recorded as MOFs.
[0072] According to the amount of guar gum, HP-UiO-66-MoS4 and sodium tetraborate in Table 1 below, the test of Examples 2 to 34 was carried out according to the scheme shown in Example 1. In this part, only the amount of the three raw materials was changed, and other parameter conditions were not changed.
[0073] Table 1 Different dosages of guar gum, HP-UiO-66-MoS4(HUM) and sodium tetraborate
[0074] Guar Gum HUM Sodium Tetraborate Guar Gum HUM Sodium Tetraborate Example 2 150mg 0.5g 4g Embodiment 19 150mg 0.5g 7g Example 3 150mg 0.5g 8g Embodiment 20 150mg 1g 2g Example 4 150mg 0.5g 12g Embodiment 21 150mg 1g 3g Example 5 150mg 0.5g 16g Embodiment 22 150mg 1g 4g Example 6 250mg 0.5g 4g Embodiment 23 150mg 1g 5g Example 7 250mg 0.5g 8g Embodiment 24 150mg 1g 6g Example 8 250mg 0.5g 12g Embodiment 25 150mg 1g 7g Example 9 250mg 0.5g 16g Embodiment 26 150mg 1.5g 2g Example 10 350mg 0.5g 4g Embodiment 27 150mg 1.5g 3g Embodiment 11 350mg 0.5g 8g Embodiment 28 150mg 1.5g 4g Example 12 350mg 0.5g 12g Embodiment 29 150mg 1.5g 5g Embodiment 13 350mg 0.5g 16g Embodiment 30 150mg 1.5g 6g Embodiment 14 150mg 0.5g 2g Embodiment 31 150mg 1.5g 7g Embodiment 15 150mg 0.5g 3g Embodiment 32 150mg 0.5g 4g Example 16 150mg 0.5g 4g Embodiment 33 150mg 1g 4g Embodiment 17 150mg 0.5g 5g Embodiment 34 150mg 1.5g 4g Embodiment 18 150mg 0.5g 6g
[0075] Comparative Example 1
[0076] S1. Preparation of UiO-66 with mixed ligands: At room temperature, 0.2331 g (1 mmol) of zirconium chloride was fully dissolved in 10 mL of N, N-dimethylformamide to obtain a zirconium chloride solution, and 0.1163 g (0.7 mmol) of terephthalic acid and 0.0544 g (0.3 mmol) of 2-aminoterephthalic acid were fully dissolved in 10 mL of N, N-dimethylformamide to obtain a mixed ligand solution. The mixed ligand solution was added to the zirconium chloride solution, and then 2.86 mL (50 mmol) of acetic acid and 20 μL of deionized water were added thereto to obtain a precursor solution. After ultrasound, the precursor solution was transferred to a hydrothermal reactor and placed in a 120°C oven for reaction for 24 hours. The product obtained after the reaction was centrifuged and washed twice in N, N-dimethylformamide, methanol, and deionized water, respectively, and then placed in a freeze dryer for freeze drying for 24 hours to obtain a UiO-66 material with mixed ligands.
[0077] S2. Preparation of sulfur cluster modified hierarchical pore UiO-66: 40 mg of ammonium tetrathiomolybdate was dissolved in 20 mL of deionized water, and 100 mg of UiO-66 material with mixed ligands obtained in S1 was added thereto. After ultrasonic oscillation, magnetic stirring was performed at room temperature to obtain a mixed solution, and then the mixed solution was transferred to an 80°C oven for reaction for 24 hours. The obtained product was ultrasonically washed 3 times with deionized water, then placed in a freeze dryer for 24 hours, and then subjected to high temperature treatment at 350°C for 2 hours to obtain sulfur cluster modified hierarchical pore UiO-66, recorded as HP-UiO-66-MoS4.
[0078] S3, preparation of gel ball loaded sulfur cluster multi-level porous MOFs composite material: take 400mg sodium alginate and dissolve it in 20mL water, then add 0.5g HP-UiO-66-MoS4 material to it respectively, and stir it magnetically to obtain a mixed solution. Take three portions of 6.6g polyvinyl alcohol and dissolve them in 200mL water respectively. After fully dissolved, add 3.76g calcium chloride to them respectively, and stir magnetically slowly at room temperature. Use a syringe to absorb a certain amount of the mixed solution of MOFs material and slowly add it dropwise to the calcium chloride solution to obtain a yellow-brown gel ball. After the obtained gel ball is stirred and washed twice with pure water, it is placed in a freeze dryer and freeze-dried for 48h to obtain a gel ball loaded sulfur cluster multi-level porous MOFs composite material, recorded as MOFs.
[0079] Comparative Example 2
[0080] This comparative example is basically the same as comparative example 1, except that the amount of HP-UiO-66-MoS4 material used in "S3, preparation of gel ball-loaded sulfur cluster multi-porous MOFs composite material" is 1 g.
[0081] Comparative Example 3
[0082] This comparative example is basically the same as comparative example 1, except that the amount of HP-UiO-66-MoS4 material used in "S3, preparation of gel ball-loaded sulfur cluster multi-level porous MOFs composite material" is 1.5 g.
[0083]
Performance test
[0084] 1. BET test
[0085] The sulfur cluster multi-level porous MOFs composite material obtained in Example 1 was subjected to BET measurement, and the results are as follows: Figure 1 shown. Figure 1 a indicates that the specific surface area of the material after calcination has dropped significantly, but the specific surface area after calcination can still be maintained at 653.2 m 2 / g, which has certain advantages for the subsequent synthesis of gel ball-loaded sulfur cluster multi-level porous MOFs composite materials. Figure 1 b It can be seen that the prepared gel ball loaded sulfur cluster multi-level porous MOFs composite material has an obvious multi-level porous structure, and while maintaining the original microporous structure, it also has mesopores of about 4nm. Theoretically, the multi-level porous structure can solve the interference of dissolved organic matter and coexisting anions and cations in complex water environments, and ensure the mass transfer efficiency of the gel ball loaded sulfur cluster multi-level porous MOFs composite material. Therefore, the emergence of the multi-level porous structure undoubtedly has great advantages for mercury adsorption.
[0086] 2. Raw material screening
[0087] Take 5 mg of the materials obtained in Examples 2 to 34 and Comparative Examples 1 to 3 and add 10 mL of a 10 mg·L mercury ion concentration -1 / 50mg·L -1 / 100mg·L -1 / 200mg·L -1 / 300mg·L -1 / 500mg·L -1 Laboratory preparation of Hg(II) solution (wherein the original Hg(II) solution is prepared by dissolving ~2.72 g of mercuric chloride in 2000 mL of deionized water to obtain a Hg(II) concentration of 1 g·L -1 The following adsorption performance test was carried out using a solution of (all mercury-containing water samples were obtained by diluting this water sample).
[0088] ① Guar gum, HP-UiO-66-MoS4 and sodium tetraborate dosage
[0089] In this section, the deep removal experiment uses 10 mg·L -1 Laboratory Hg(II) solution; 100 mg·L for adsorption capacity experiments -1 Laboratory Hg(II) solution; 10 mg·L for thermodynamic adsorption experiments -1 / 50mg·L -1 / 100mg·L -1 / 200mg·L -1 / 300mg·L -1 / 500mg·L -1 Laboratory Hg(II) solution.
[0090] The actual photos of the gel ball-supported sulfur cluster multi-level porous MOFs composite materials obtained in Examples 2 to 13 were taken and recorded in Figure 2 Observation Figure 2 It can be seen that: with the increase of the amount of guar gum and sodium tetraborate, the aggregation force of the gel spheres is enhanced, while the volume of the spheres is gradually reduced. In addition, further adsorption experiments were carried out on the gel spheres obtained in Examples 2 to 13, and the results are as follows: Figure 3 Observation Figure 3 It can be seen that the Hg(II) adsorption performance decreases with the increase of guar gum dosage, 150 mg guar gum is the best, while the dosage of sodium tetraborate is around 4 g.
[0091] After obtaining the above proportion concept, the applicant conducted the next experiment: to determine the effect of different amounts of sodium tetraborate and different MOF materials (HP-UiO-66-MoS4, HUM) on the gel ball-loaded sulfur cluster multi-level porous MOFs composite material. Figure 4 It can be seen that as the amount of sodium tetraborate increases, the aggregation force of the gel spheres increases, the color gradually deepens, and the volume of the spheres gradually decreases. Further adsorption experiments were carried out on the materials obtained in Examples 14 to 31. Figure 5 It can be seen that the Hg(II) adsorption performance of the material is optimal when the dosage of sodium tetraborate is 4g, and the loading amount of MOFs material is optimal when it is 1g.
[0092] The apparent and microscopic determination results of the materials obtained in Examples 32 to 34 are as follows Figure 6 As shown, it can be observed that the formed material is a relatively complete sphere with a smooth surface. Figure 7 It can be seen that the materials obtained in Examples 32 to 34 all have a multi-level pore structure, and as the loading amount of the MOFs material increases, its specific surface area increases slightly. When the loading amount increases to 1g, its specific surface area no longer increases significantly. Subsequently, the materials obtained in Examples 32 to 34 were subjected to thermodynamic adsorption measurement, and it was observed that Figure 8 It can be seen that with the increase in the loading amount of MOFs material, the adsorption capacity of the obtained material gradually increases; this result corresponds to the result of BET, that is, the higher the loading amount of MOFs, the larger the specific surface area of the material and the greater the adsorption capacity.
[0093] ② Sodium alginate drop ball method comparison
[0094] In this part, the thermodynamic adsorption experiments were performed with 10 mg·L -1 / 50mg·L -1 / 100mg·L -1 / 200mg·L -1 / 300mg·L -1 / 500mg·L -1 Laboratory Hg(II) solution; 10 mg·L for kinetic experiments -1 Laboratory Hg(II) solution.
[0095] The materials obtained in Comparative Examples 1 to 3 were subjected to thermodynamic adsorption measurement, and the results are as follows: Fig. 9 Observation Fig. 9 It can be seen that with the increase of MOFs material loading, the adsorption capacity of the material gradually increases; Figure 8 By comparison, the results show that at the same loading amount, the adsorption capacity of sodium alginate gel ball material is much lower than that of guar gum gel ball material.
[0096] The materials obtained in Comparative Examples 1 to 3 were subjected to adsorption kinetics measurement, and the results are as follows: Fig.10 Observation Fig.10 It can be seen that the adsorption rate of guar gum gel balls is much better than that of sodium alginate gel balls.
[0097] 3. Adsorption experiment
[0098] Take 5 mg of the material obtained in Example 1 and add 10 mL of mercury ion concentration 10 mg·L -1 / 50mg·L -1 / 100mg·L -1 / 200mg·L -1 / 300mg·L -1 / 500mg·L -1 Laboratory preparation of Hg(II) solution (wherein the original Hg(II) solution is prepared by dissolving ~2.72 g of mercuric chloride in 2000 mL of deionized water to obtain a Hg(II) concentration of 1 g·L -1 The following adsorption performance test was carried out using a solution of (all mercury-containing water samples were obtained by diluting this water sample).
[0099] ①XRD
[0100] This part uses 500mg·L-1 The sample with saturated adsorption was obtained by using Hg(II) solution in the laboratory. The dosage of the material obtained in Example 1 was 1 g·L -1 .
[0101] Comparative analysis of the XRD of the material obtained in Example 1 before and after adsorption revealed that: Fig.11 Middle: The obtained material has the carbon structure characteristics of organic matter before adsorption, while the characteristic peak of HgCl appears after adsorption.
[0102] ② Temperature
[0103] In this part, the thermodynamic adsorption experiments were performed with 10 mg·L -1 / 50mg·L -1 / 100mg·L -1 / 200mg·L -1 / 300mg·L -1 / 500mg·L -1 Laboratory Hg(II) solution.
[0104] The materials obtained in Example 1 were compared and analyzed at different adsorption treatment temperatures. The results are as follows: Fig.12 As shown: As the temperature increases, the adsorption performance of the material improves.
[0105] ③pH
[0106] In this section, 10 mg·L -1 Laboratory Hg(II) solution.
[0107] The materials obtained in Example 1 were compared and analyzed under different adsorption treatment environment pH. The results are as follows: Fig.13 As shown: In a wide pH range (1-12), the material exhibits excellent removal rate for Hg(II).
[0108] ④Cation
[0109] In this section, 10 mg·L -1 / 50mg·L -1 Laboratory Hg(II) solution.
[0110] The materials obtained in Example 1 were compared and analyzed under different adsorption treatment environments with cation interference. The results are as follows: Figures 14-15 As shown: the material has excellent anti-interference ability of coexisting cations; and the material has the strongest adsorption and binding force for Hg(II) and has excellent Hg(II) selectivity.
[0111] ⑤ Anions
[0112] In this section, 10 mg·L -1 Laboratory Hg(II) solution.
[0113] The materials obtained in Example 1 were compared and analyzed under different adsorption treatment environments with anion interference. The results are as follows: Fig.16 Shown: The material has excellent anion anti-interference ability.
[0114] ⑥Organic matter
[0115] In this section, 10 mg·L -1 Laboratory Hg(II) solution.
[0116] The materials obtained in Example 1 were compared and analyzed under different organic matter interference in the adsorption treatment environment. The results are as follows: Fig.17 As shown: Under high concentration organic matter conditions, the Hg(II) removal performance of the material is still higher than that of traditional adsorbent materials, which is due to the distribution of multi-level pores in the material and its excellent hydrophilicity.
[0117] ⑦Industrial wastewater
[0118] In this section, 10 mg·L -1 Laboratory Hg(II) solution.
[0119] Fig.18 The three types of industrial wastewater used in the study (corresponding to codes 1, 2, and 3) come from different links of the heavy metal treatment process in zinc and lead smelting plants. Among them, wastewater No. 1 (pH = 0.68) comes from the washing acid circulation liquid of the zinc smelting plant, wastewater No. 2 (pH = 1.42) comes from the direct refining acid wastewater of the lead smelting plant, and wastewater No. 3 (pH = 1.60) comes from the direct refining acid denitrification wastewater of the lead smelting plant. In addition to mercury, these industrial wastewaters also contain a variety of coexisting heavy metal ions (such as arsenic ions, lead ions, copper ions, cadmium ions, sodium ions, potassium ions, calcium ions, etc.).
[0120] The material obtained in Example 1 was subjected to adsorption treatment of industrial wastewater and it was found that: Fig.18 Even under strong acid (0.68) conditions, the removal rate of the material is still as high as 99.6%, indicating that the material has excellent practical Hg(II) wastewater treatment capabilities.
[0121] ⑧Cycling performance
[0122] This section uses 10 mg·L -1 The sample with saturated adsorption was obtained by using Hg(II) solution in the laboratory. The dosage of the material obtained in Example 1 was 1 g·L -1 The desorption liquid is a mixed solution of 0.01 mol / L hydrochloric acid and 1% wt thiourea.
[0123] The material obtained in Example 1 was subjected to cyclic adsorption treatment and it was found that: Fig.19In the experiment, the removal effect of the material still reached 90% after 5 cycles, and the removal effect of the material was also above 80% after 10 cycles, indicating that the material has good recycling ability.
Claims
1. A gel ball-loaded sulfur cluster multi-level porous MOFs composite material, characterized in that: It comprises a skeleton and a guar gum gel layer wrapped on the skeleton, wherein the mass ratio of the skeleton to the guar gum gel layer is (0.5-1.5):(2.15-16.35); the skeleton is composed of a multi-level porous UiO-66 material modified by sulfur clusters, and the multi-level porous UiO-66 material has micropores and mesopores; The preparation method of the gel ball-loaded sulfur cluster multi-level porous MOFs composite material is as follows: S1. Adding UiO-66 with mixed ligands to ammonium tetrathiomolybdate solution, mixing evenly, reacting, freeze-drying, and calcining to obtain sulfur cluster-modified hierarchical porous UiO-66; S2. The mixed solution obtained by mixing the sulfur cluster modified multi-level porous UiO-66 obtained in S1 with guar gum solution is dropped into a sodium tetraborate solution to obtain gel balls. After washing and collection, the gel balls are freeze-dried to obtain a gel ball-loaded sulfur cluster multi-level porous MOFs composite material; the dry weight mass ratio of the sulfur cluster modified multi-level porous UiO-66, guar gum, and sodium tetraborate is (0.5~1.5):(0.15~0.35):(2~16).
2. The gel ball-supported sulfur cluster multi-level porous MOFs composite material according to claim 1, characterized in that: The modification amount of the sulfur clusters is 4-5%wt, the pore diameter of the mesopores is 2.5-4.5 nm, and the number ratio of the micropores to the mesopores is (1.8-2.2):
1.
3. The method for preparing the gel ball-supported sulfur cluster multi-level porous MOFs composite material according to claim 1, characterized in that: include: S1. Adding UiO-66 with mixed ligands to ammonium tetrathiomolybdate solution, mixing evenly, reacting, freeze-drying, and calcining to obtain sulfur cluster-modified hierarchical porous UiO-66; S2. The mixed solution obtained by mixing the sulfur cluster modified multi-level porous UiO-66 obtained in S1 with guar gum solution is dropped into a sodium tetraborate solution to obtain gel balls. After washing and collection, the gel balls are freeze-dried to obtain a gel ball-loaded sulfur cluster multi-level porous MOFs composite material; the dry weight mass ratio of the sulfur cluster modified multi-level porous UiO-66, guar gum, and sodium tetraborate is (0.5~1.5):(0.15~0.35):(2~16).
4. The preparation method according to claim 3, characterized in that: In S1, the preparation method of UiO-66 with mixed ligands includes: dissolving a zirconium source, a stable ligand, and an unstable ligand in an organic solvent, adding an acetic acid aqueous solution, mixing, and then performing a hydrothermal reaction.
5. The preparation method according to claim 3 or 4, characterized in that: In S1, the reaction conditions are 70-100° C. for 24-48 h; and the calcination conditions are 340-400° C. for 2-4 h.
6. Use of the gel ball-supported sulfur cluster multi-level porous MOFs composite material as described in claim 1 or 2 or the gel ball-supported sulfur cluster multi-level porous MOFs composite material prepared by the preparation method according to any one of claims 3 to 5 in removing Hg(II) from mercury-contaminated water.
7. The use according to claim 6, characterized in that The mercury-contaminated water is a natural water body containing mercury; the temperature of the natural water body containing mercury is 15-35° C., the pH is 1-12, and it contains a variety of anions, a variety of cations, and a variety of organic matter.
8. The use according to claim 6, characterized in that The mercury-contaminated water is industrial wastewater containing mercury; the pH of the industrial wastewater is 0.68-1.
6.
9. The use according to any one of claims 6 to 8, characterized in that: The gel ball-loaded sulfur cluster multi-level porous MOFs composite material can cyclically adsorb and remove mercury-contaminated water.
Citation Information
Patent Citations
Preparation method and application of multifunctional biomass-based composite hydrogel
CN110433737A
Surfactant-MOF composite material and preparation method thereof
CN113583647A